The phylogenetic similarity of hydatid cyst isolated from humans and sheep in Ilam Province southwest of Iran. (November 2016) - Shamsi, Morteza; Dalimi, Abdolhossein; Khosravi, Afra; Ghafarifar, Fatemeh
Abstract Hydatid cyst is a chronic zoonotic disease caused by the larval stage of the dog tapeworm, Echinococcus granulosus . To identify genotype of hydatid cysts of human and sheep jackal in Ilam Province (South West of Iran), the PCR-RFLP and DNA sequencing were used. A total of 10 human and 20 sheep protoscoleces hydatid cyst samples were collected from different hospitals and slaughterhouses. Then, the gene of cox1 of mitDNA of the parasite was amplified and PCR products were cut usingAluI and HpaII restriction enzymes. Finally, a number of PCR products were bi-directionally sequenced. Based on the DNA sequencing and PCR-RFLP results, human and sheep samples indicated to pertain the genotypic similarities. Our data indicated that, the genotypes of larval stage ofE. granulosus is similar in both intermediate hosts. According to the phylogenetic tree, there is at least one genotype of parasite, which belongs toE. granulosous sensu stricto (G1–G3) complex and overall isolates sequences of mtDNA indicated 100 % homology with references G1, G2, and G3 sequences in the GenBank database. G1 genotype was the dominant genotype of human and livestock.